A Low-Impact Development–Based Multi-Objective Optimization Model for Regional Water Resource Management under Impacts of Climate Change - Bao, Zhe; Yang, Hansheng; Li, Wei; Xu, Ye; Huang, Guohe (Frontiers in Earth Science, 2020)
Under the urgency of rational water resource allocation and effective urban flooding control, a multi-objective interval birandom chance-constrained programming (MIBCCP) model is developed for supporting regional water resource management under multiple uncertainties and climate change in this study. Two objectives were included in this model, which are the minimization of total system costs and the maximization of total pollutant-treatment amounts, respectively. The major advantage of proposed MIBCCP model is that it realized the effective combined utilization of conventional and nonconventional water sources under complexities and uncertainties through incorporating compromise programming (CP), birandom chance-constrained programming (BCCP) and interval linear programming (ILP) within a general framework. This way effectively overcome water-shortage issue and reduced urban flood frequency under climate change. A water supply management system of the educational park in Tianjin was used as a study case for demonstration. A variety of adaptive water allocation alternatives and construction schemes for LID projects under RCP4.5 and RCP8.5 (representative concentration pathway 4.5 and 8.5) scenarios were obtained to deal with possible changes arising from increasing rainfall and runoff in the future. It is concluded that proposed MIBCCP model provided the effective linkage between the utilization of nonconventional water resources and urban flood prevention, and offered insights into the tradeoff between economic benefits and environmental protection.